Phonological Adaptation Of The Belgian French Vowels In Kinshasa Lingala - Kabasele, Philothé Mwamba (My University, 2022)
This study provides a systematic analysis of vowel sound adaptations in KL with evidence from acoustic phonetics. The research is restricted to the phonological adaptations of vowel sounds from Belgian French (BF). It provides evidence from loan data on the existence of the contrastive features [±ATR] in KL phonological system. Questions raised include: does the phonological system of KL take precedence in the phonological adaptation process of the loanwords? Does similarity play a role in the adaptation of the loanwords? What happens when the foreign input does not offer any similarity with the phonological system of the recipient language (RL)? what happens when a feature/feature combination (FC) in a foreign input vowel either presents similarities with a feature/FC in the RL phonological system, or else does not present any similarities to any feature or FC in the phonological system of the RL? The data were extracted in a sentential context with a carrier sentence. Participants filled in the dots with the missing word that was suggested by the picture. The F1 and the F2 measurement values, in hertz (Hz) were taken at three different points of the vowel spectrogram. The script also generated the average measurement values which were considered as input for statistical analysis. The null hypothesis (Ho) predicts that BF [ɛ, œ, ø] would be adapted as [e] (Ho: [ɛ] = [e], [œ] = [e], and [ø] = [e]) in KL, while the alternative hypothesis (H1) predicts that the BF vowels [ɛ, œ, ø] would not be adapted as [e] (H1: [ɛ] ≠ [e], [œ] ≠ [e], and [ø] ≠ [e]) in KL. The Ho predicts that [ɔ] will be adapted as [o] (Ho: [ɔ] = [o]). Due to correlated nature of the data, Generalized Estimating Equation (GEE) was used to determine the degree of significant differences between two/more targeted variables. The findings have shown that KL speakers still discriminate between [ɛ] and [e], and [ɔ] and [o], which implies the existence of the underlying contrast between the features [+ATR] and [−ATR].
Keywords: Belgian French vowels; Kinshasa Lingala; Phonological adaptation